Penerapan Analisis Cost Volume Provit (CVP) dalam Perencanaan Produksi - Rahmi, Mega; Satria, Ileh; Nisa, Putri Khairul; Karmila, Rena; Putri, Riza Yulia; Yaqin, Syarifa Ainul (CV. Ulil Albab Corp, 2025)
This study aims to analyze the application of Cost Volume Profit (CVP) analysis as a basis for production planning and decision-making in the UMKM Kue Kacang Putri Nisa. The main issues faced by the business include the inability to identify cost structures accurately, suboptimal pricing strategies, and the absence of break-even and profit-target analysis in planning. This research applies a quantitative approach through interviews, observations, and documentation to obtain data regarding fixed costs, variable costs, sales volume, and profit levels. The results indicate that the business is able to cover all expenses and generate a net profit of Rp 6,943,833 under normal production conditions. The break-even point is achieved at 1,086 units, while a profit target of Rp 8,000,000 requires sales of 29,658 units. Furthermore, the Margin of Safety and Operating Leverage values show that the business operates with relatively low risk and stable profit sensitivity. In conclusion, CVP analysis effectively supports the UMKM in optimizing production strategies, controlling costs, and setting realistic profit targets to strengthen profitability and business competitiveness.